EMBEDDING GAMIFICATION IN MODERN PEDAGOGICAL FRAMEWORKS - Tokhtamisheva Sevinch Kamilovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study explores the pedagogical potential of gamification in modern education. Integrating game elements such as points, levels, badges, and leaderboards into learning enhances student motivation and engagement. The research is based on a theoretical review of literature on gamification and educational technology. Findings suggest that gamification supports active participation and improves learning outcomes.